Thermal and Mechanical Analysis of Bimodular Beam - Shah S.; Panda S.K. (My University, 2025)
The paper demonstrates the analysis of cantilever beam having dissimilar modularity in tensile and compressive tests liable with thermal and mechanical loading. The prime objective is to evaluate the governing differential equations to determine the displacements of the bimodular beam under combined loading of thermal and mechanical loading. The relation between change in temperature for conduction and convection for particular value of length of cantilever beam has been assessed. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.